O uso da avaliação formativa : uma revisão quantitativa da produção científica brasileira (2010-2015) - Schmitz, Heike (2017)
The topic of this article is the formative evalution with focus on the feedback given by and for the student. Recent Brazilian scientific publications (2010-2015) have been analyzed quantitatively in order to investigate their findings on possible techniques and instruments as feedback tools for the teaching-learning process. A number of 38 empirical scientific studies have been analyzed: 36,3% of these studies explicitly discuss a specific evaluation technique or instrument; 26,3 % indicated forms of evaluation which allow the student’s autonomous participation in the evaluation process; 26,3% focus on the student’s role in this process, and 63,1 % focus on the role of the teacher. The analyzed researches were predominantly case studies of qualitative character. The knowledge acquired through case studies is valid, but it does not paint a broad picture of the Brazilian educational system which could allow to deduce considerations in respect to the teacher's training.